A special issue of Essays in Biochemistry on current advances about CAZymes and their impact and key role in human health and environment - Czjzek, Mirjam; Ficko-Blean, Elizabeth; Berrin, Jean-Guy (Essays in biochemistry, 2023)
Carbohydrate active enzymes (CAZymes) and their biochemical characterization have been the subject of extensive research over the past ten years due to their importance to carbohydrate metabolism in different biological contexts. For instance, the understanding that 'polysaccharide utilizing loci' (PUL) systems hosted by specific 'carbohydrate degraders' in the intestinal microbiota play key roles in health and disease, such as Crohn's disease, ulcerative colitis or colorectal cancer to name the most well-characterized, has led to an outstanding effort in trying to decipher the molecular mechanisms by which these processes are organized and regulated. The past 10 years has also seen the expansion of CAZymes with auxiliary activities, such as lytic polysaccharide monooxygenases (LPMOs) or even sulfatases, and interest has grown in general about the enzymes needed to remove the numerous decorations and modifications of complex biomass, such as carbohydrate esterases (CE). Today, the characterization of these 'modifying' enzymes allows us to tackle a much more complex biomass, which presents sulfations, methylations, acetylations or interconnections with lignin. This special issue about CAZyme biochemistry covers all these aspects, ranging from implications in disease to environmental and biotechnological impact, with a varied collection of twenty-four review articles providing current biochemical, structural and mechanistic insights into their respective topics.